Keys to The Gift A Guide to Vladimir Nabokov's Novel - Leving, Yuri (Academic Studies Press, 2011)
"Yuri Leving's Keys to The Gift: A Guide to Vladimir Nabokov's Novel is a new systematization of the main available data on Nabokov's most complex Russian novel, The Gift (1934-1939). From notes in Nabokov's private correspondence to scholarly articles accumulated during the seventy years since the novel's first appearance in print, this work draws from a broad spectrum of existing material in a succinct and coherent way and provides innovative analyses. The first part of the monograph, "The Novel," outlines the basic properties of The Gift (plot, characters, style, and motifs) and reconstructs its internal chronology. The second part, "The Text," describes the creation of the novel and the history of its publication, public and critical reaction, challenges of English translation, and post-Soviet reception. Along with annotations to all five chapters of The Gift, the commentary provides insight into problems of paleography, featuring a unique textological analysis of the novel."
Description based on print version record.
KU Open Services
Keywords: Literary Collections; Anthologies; Electronic books